Effectiveness of humanistic learning models on intra and interpersonal intelligence - GASONG, D.; TODING, A. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study describes the affective aspects of learning that have not yet been developed. Its purpose firstly is to describe the problem of the low ability of students to express their ideas well. Secondly, this study designs a humanistic learning model that can be implemented in lectures so students can get to know themselves and others (intrapersonal and interpersonal). The method used in this study is qualitative. The results of it are as follows: The cause of low intrapersonal and interpersonal intelligence is because so far, only practicing to do things related to knowledge. Students only try to pursue education. RESUMEN Este estudio describe los aspectos afectivos del aprendizaje que aún no se han desarrollado. En primer lugar, su propósito es describir el problema de la baja capacidad de los estudiantes para expresar bien sus ideas. En segundo lugar, este estudio diseña un modelo de aprendizaje humanista que puede implementarse en conferencias para que los estudiantes puedan conocerse a sí mismos y a los demás (intrapersonal e interpersonal). El método utilizado en este estudio es cualitativo. Los resultados son los siguientes: la causa de la baja inteligencia intrapersonal e interpersonal es porque, hasta ahora, solo practica hacer cosas relacionadas con el conocimiento. Los estudiantes solo intentan seguir la educación.